Effect of Alchornea cordifolia on Glycemic Indices of Varieties of Fufu Among Healthy Subjects - Otoo, Eunice T; Tandoh, Marina A; Mills-Robertson, Felix C (Current developments in nutrition, 2024)
Glycemic index (GI) is a measure of the ability of carbohydrate food to raise blood glucose concentration. The GI of a food and its negative effects has caused an adverse increase in the prevalence of diabetes and other metabolic diseases. This study aimed to determine the effect of Alchornea cordifolia on glycemic indices of varieties of fufu. The research was a crossover experimental study involving 10 healthy individuals. A 50-g measure of pure glucose was served on 2 separate occasions and, subsequently, a measured amount of the test foods containing 50 g of available carbohydrates. The GI values were determined by the measure of the blood glucose concentrations of the subjects at fasting and after ingestion of the glucose and the test foods (fufu) within 2 h. Collection of capillary blood for blood glucose measurement started 30 min after consumption and was subsequently taken at 60, 90, and 120 min for both noncomposited and composited fufu GI determination. The phytoconstituents of the A. cordifolia were also determined. For the noncomposited fufu, plantain fufu had the least glycemic response (46%), followed by cassava fufu (50%) and cassava–plantain fufu (53%); however, all were in the low-GI category. For the composited fufu, plantain fufu had the least response (12%), followed by cassava–plantain fufu (14%) and cassava fufu (14%), with all in the low-GI category. A multiple comparison of GI on the various foods by analysis of variance revealed a significant difference between the GI of cassava–plantain fufu and composite cassava–plantain fufu (P = 0.001); cassava fufu and composite cassava fufu (P = 0.004); and plantain fufu and composite plantain fufu (P = 0.006). The phytochemical screening of the A. cordifolia revealed the presence of flavonoids and tannins. Composited A. cordifolia fufu affects the glycemic response.